Polymorphisms in the estrogen receptor alpha gene (ESR1), daily cycling estrogen and mammographic density phenotypes. Issue 1 (December 2016) - Fjeldheim, F.; Frydenberg, H.; Flote, V.; McTiernan, A.; Furberg, A-S; Ellison, P.; Barrett, E.; Wilsgaard, T.; Jasienska, G.; Ursin, G.; Wist, E.; Thune, I.
Abstract Background Single nucleotide polymorphisms (SNPs) involved in the estrogen pathway and SNPs in the estrogen receptor alpha gene (ESR16q25 ) have been linked to breast cancer development, and mammographic density is an established breast cancer risk factor. Whether there is an association between daily estradiol levels, SNPs inESR1 and premenopausal mammographic density phenotypes is unknown. Methods We assessed estradiol in daily saliva samples throughout an entire menstrual cycle in 202 healthy premenopausal women in the Norwegian Energy Balance and Breast Cancer Aspects I study. DNA was genotyped using the Illumina Golden Gate platform. Mammograms were taken between days 7 and 12 of the menstrual cycle, and digitized mammographic density was assessed using a computer-assisted method (Madena). Multivariable regression models were used to study the association between SNPs inESR1, premenopausal mammographic density phenotypes and daily cycling estradiol. Results We observed inverse linear associations between the minor alleles of eight measured SNPs (rs3020364, rs2474148, rs12154178, rs2347867, rs6927072, rs2982712, rs3020407, rs9322335 ) and percent mammographic density (p -values: 0.002–0.026), these associations were strongest in lean women (BMI, ≤23.6 kg/m2. ). The odds of above-median percent mammographic density (>28.5 %) among women with major homozygous genotypes were 3–6 times higher than those of women with minor homozygous genotypes in seven SNPs. Women withrs3020364 major homozygous genotype had an OR of 6.46 for above-median percent mammographic density (OR: 6.46; 95 % Confidence Interval 1.61, 25.94) when compared to women with the minor homozygous genotype. These associations were not observed in relation to absolute mammographic density. No associations between SNPs and daily cycling estradiol were observed. However, we suggest, based on results of borderline significance (p values: 0.025–0.079) that the level of 17β-estradiol for women with the minor genotype forrs3020364, rs24744148 andrs2982712 were lower throughout the cycle in women with low (<28.5 %) percent mammographic density and higher in women with high (>28.5 %) percent mammographic density, when compared to women with the major genotype. Conclusion Our results support an association between eight selected SNPs in theESR1 gene and percent mammographic density. The results need to be confirmed in larger studies.